PERAN MINDFULNESS UNTUK MENGATASI FEAR oF MISSING OUT (FoMO) MEDIA SOSIAL REMAJA GENERASI Z : TINJAUAN LITERATUR - Utami, Ferisa Prasetyaning (Universitas Borneo Tarakan, 2022)
Adolescents belonging to Generation Z live and are born in the era of social media. The existence of social media makes generation Z teenagers have the characteristics of socializing which is done online. The impact of the intensity that is too high to be socially connected on social media makes teenagers experience Fear of Missing Out (FoMO), namely the fear of teenagers to miss information that is viral and the tendency to compare themselves (Self-comparison) with others on social media. Adolescents who experience FoMO show negative emotions such as stress, anxiety and anxiety. This study is a literature review that discusses the role of mindfulness on the fear of missing out (FoMO) of social media in generation Z adolescents. Based on the literature review conducted, the practice of mindfulness is divided into two, namely formal and informal. The application of mindfulness practices will provide changes to three axioms, namely attention, intention and attitude to individuals, especially in the context of overcoming FoMO.Keywords : Mindfulness; Fear of Missing Out; Adolescence; Z Generation; Social Media